2015
DOI: 10.15761/icst.1000144
|View full text |Cite
|
Sign up to set email alerts
|

Pleurodesis in malignant pleural effusions: Outcome and predictors of success

Abstract: Malignant pleural effusion is a common clinical problem in cancer patients. Many therapeutic techniques have been investigated, including pleurodesis. Little is known about the factors that may affect the success rate of such a procedure. The main objective of this study is to assess the success rates of pleurodesis performed on malignant pleural effusions in cancer patients at AUBMC and to identify the predictors of a successful pleurodesis. Patients diagnosed with malignant pleural effusions and who have und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 21 publications
2
11
1
Order By: Relevance
“…Although LDH mean value in failed cases was higher than succeeded cases, the difference between them did not reach statistical significance (p=0.41). These results were in concordance with the results obtained in the study performed by Ferreiro et al [ 8 ], Yildirim et al [ 11 ], and Rafei et al [ 12 ], who found no correlation between the values of pleural fluid LDH and the success or failure of pleurodesis.…”
Section: Discussionsupporting
confidence: 93%
“…Although LDH mean value in failed cases was higher than succeeded cases, the difference between them did not reach statistical significance (p=0.41). These results were in concordance with the results obtained in the study performed by Ferreiro et al [ 8 ], Yildirim et al [ 11 ], and Rafei et al [ 12 ], who found no correlation between the values of pleural fluid LDH and the success or failure of pleurodesis.…”
Section: Discussionsupporting
confidence: 93%
“…These factors were found to have a strong negative impact on the success of the procedure regardless of the method of pleurodesis used. Santos et al and Rafei et al in their studies (21,22) concluded that both age and gender have no significant effects over pleurodesis outcomes. This might be partially true regarding age as an independent factor.…”
Section: Discussionmentioning
confidence: 97%
“…Procedure success and complete response to treatment was defined based on Rafei et al [4] works in 2015. Complete response is defined as the absence of fluid accumulation that requires repeated thoracocentesis/chest tube drainage in the follow up imaging (chest X-ray or CT thorax).…”
Section: Methodsmentioning
confidence: 99%